Clinical, genotypic, and neuropsychological profile in a series of patients with Niemann-Pick type C disease - dos Santos Mendes, Rita; do Valle, Daniel Almeida; dos Santos Bara, Tiago; Furlin, Vanessa; da Silva Zeny, Michelle; Schmitz Ferreira Santos, Mara Lúcia; Cordeiro, Mara L. (Frontiers in Neurology, 2025)
BackgroundNiemann-Pick type C (NPC) disease is a rare neurodegenerative disorder with a wide spectrum of clinical manifestations and genetic variability. This cross-sectional study aimed to comprehensively describe the neuropsychological impact of NPC and investigate its correlation with specific genotypes.ResultsEight patients from six unrelated families were included in this study. Their age at symptom onset ranged between 2 and 16 years, with all patients presenting with ataxia, dysarthria, and cognitive impairment. Following the initiation of miglustat treatment, five patients showed a decrease in the Scale for the Assessment and Rating of Ataxia (SARA) score, whereas three demonstrated subsequent increases. Five patients underwent brain magnetic resonance imaging scans, revealing white matter abnormalities and/or brain volumetric reduction in three cases. Despite the small sample size, the overall cognitive performance of the cohort was significantly below the average. The Family Environment Scale highlighted positive structural patterns, particularly regarding Personal Growth and System Maintenance. Genetic analysis identified five mutations in the NPC1 gene that correlated with the severity of impairments and clinical outcomes.ConclusionThis study indicated a consistent association between cognitive and behavioral impairments, with severity correlating with age and specific genetic variants. Notably, one subgroup showed a higher prevalence of psychotic and behavioral symptoms, suggesting a potential link with specific genetic variants.